An Action Research on Enacting Play-based Pedagogy in a Pre-service Teachers' Art Classroom - (:unkn) unknown (My University, 2017)
As a school-based art educator, I advocate for an educational environment that embraces and values concepts of play and play-based pedagogy and encourage understandings of the significant role of play in teaching and learning and its relation to art, artifacts, and multiculturalism. This thesis documents an action research project, reflecting a dialogue about play-based art education in a college classroom. As a social constructivist and an advocate for multiculturalism, I introduced knowledge on play-based pedagogy and its benefits to college students and studied my practices in relation to student learning, especially those students in pre-service teacher education programs. Concepts associated with play included true or authentic play, material rich environmental learning, integration of play with art and other disciplines, and multiculturalism and in relation to social and cultural contexts. The role of art and artifacts was used to build a sense of the connection between art and play and its relations. This action research helped me build a sense of practice in relationship to learners in my classroom and through two cycles of reflection on how play could be used as learning tool and as an integral of a curriculum for young children. Data was collected over the course of one semester and explored using narrative analysis, focusing on values and beliefs associated with play-based art education.
Keywords: Child Play; Emergent Curriculum; Multiculturalism; Narrative Analysis; Play-based Art Education; Social Constructivism